Evaluation of Economic Production Quantity For Continuous Production System : Case Of Chilled Water Generation, Storage And Distribution. - A Ganesh, Dinnassh (IRC, 2021)
The report presents the study on the Thermal Energy Storage (TES) system and the Electric Chillers (EC) system in Gas District Cooling (GDC) plant in UTP by adopting Economic Production Quantity (EPQ) model for the system.